Peramalan Harga Cabai dan Bawang di Pasar Tradisional Purwokerto dengan Model Autoregressive Integrated Moving Average (ARIMA) - Ulya, Fadilla Zundina; Wijaya, Andreas Rony; Puspita, Popy Laras (Seminar Nasional Official Statistics, 2023)
Chilies and onions are the agricultural commodities that are commonly used in daily life. However, fluctuating chili and onion prices can cause market instability and harm farmers when prices drop sharply. Therefore, it is necessary to conduct forecasting to predict the future price of both commodities. This research aims to find the best model for predicting chili and onion prices using the Autoregressive Integrated Moving Average (ARIMA) method which is determined based on minimum AIC and BIC values. The data used in this research includes the price of large red chilies, bird's eye chilies, shallots and garlic at the Purwokerto Traditional Market from January 2022 to April 2023. The selected models are ARIMA (0,1,0), ARIMA (1,1,0 ), ARIMA (0,1,0), and ARIMA (3,1,0) respectively for large red chilies, bird's eye chilies, shallots, and garlic. The forecasting model evaluation metrics used are RMSE and MAPE. The value is small enough to indicate that the model is appropriate. Based on the forecasting results, the price of chilies and onions in the next month will tend to be constant at IDR 55,000 for large red chilies, IDR 55,086 for bird's eye chilies, IDR 45,000 for shallots, and IDR 40,000. - for the garlic.